Time varying characteristic in somatosensory evoked potentials as a biomarker of spinal cord ischemic-reperfusion injury in rat - Li, Kai; Yang, Jianwei; Wang, Huaibo; Chang, Xuejing; Liu, Guanjun; Xue, Ruiyang; Guo, Weitao; Hu, Yong (Frontiers in Neuroscience, 2024)
Spinal cord ischemic-reperfusion injury (SCIRI) could occurs during surgical procedures without detection, presenting a complex course and an unfavorable prognosis. This may lead to postoperative sensory or motor dysfunction in areas innervated by the spinal cord, and in some cases, permanent paralysis. Timely detection of SCIRI and immediate waring can help surgeons implement remedial intervention to prevent irreversible spinal cord injury. Therefore, it is crucial to develop a precise and effective method for early detection of SCIRI. This study utilized rat models to simulate intraoperative SCIRI and employed somatosensory evoked potentials (SEP) for continuous monitoring during surgery. In this study, SEP signal changes were examined in six groups with varying severities of SCIRI and one normal control group. SEP signal changes were examined during operations in different groups and correlated with postoperative behavioral and histopathological data. The result demonstrated specific changes in SEP signals during SCIRI, termed as time-varying characteristics, which are associated with the duration of ischemia and subsequent reperfusion. Time-varying characteristics in SEP could potentially serve as a new biomarker for the intraoperative detection of SCIRI. This finding is significant for clinical surgeons to identify and guide early intervention of SCIRI timely. Additionally, this measurement is easily translatable to clinical application.